The relationship between anemia, serum hepcidin levels, and chronic hepatitis C in chronic hemodialysis patients - Maher A Al-Amir; Ahmed A Hassan; Shahira M Elshafie; Heba M Zein Elabdin; Sara A Taha (SpringerOpen, 2017)
Background Hepcidin is a small peptide that is produced by hepatocytes and circulates in the plasma. It plays a central role in regulating the iron status in the body. Aim The aim of this study was to measure serum hepcidin levels in maintenance hemodialysis (MHD) patients and identify a possible impact of chronic hepatitis C virus (HCV) infection on the severity of anemia. Patients and methods This cross-sectional study was conducted on a cohort of 80 MHD patients (40 HCV positive and 40 HCV negative) and 20 healthy age-matched and sex-matched participants who participated as normal controls. Serum hepcidin and highly-sensitive C-reactive protein were measured in patients to study their possible effect on hematological and inflammatory parameters when compared with the control group. Results MHD patients had significantly higher serum hepcidin levels than did controls. The HCV-positive group had significantly lower serum hepcidin and ferritin levels when compared with the HCV-negative group. All MHD patients had significantly higher levels of serum highly-sensitive C-reactive protein than did controls. Hepcidin was also found to correlate with age and serum ferritin levels among MHD patients. Conclusion Changes in serum hepcidin levels are associated with iron status and microinflammation in MHD patients. If used as a diagnostic tool, it may improve targeting and timing of iron therapy by identifying patients during periods of reticuloendothelial blockage of iron transport. This is important to avoid iron overload, especially in HCV-positive patients, which may otherwise cause liver injury resulting in fibrosis, cirrhosis, and finally HCC. We also revealed the value of ferritin levels, which seemed to play an important role in determining the severity of liver disease related to liver fibrosis and microinflammatory activity.